A Review of Bunyamwera, Batai, and Ngari Viruses: Understudied Orthobunyaviruses With Potential One Health Implications - Dutuze, M. Fausta; Nzayirambaho, Manassé; Mores, Christopher N.; Christofferson, Rebecca C. (Frontiers in Veterinary Science, 2018)
Bunyamwera (BUNV), Batai (BATV), and Ngari (NRIV) are mosquito-borne viruses of the Bunyamwera serogroup in the Orthobunyavirus genus of the Bunyaviridae family. These three viruses have been found to cause disease in both livestock animals, avian species, and humans. Thus, these viruses pose a potential threat to human public health, animal health, and food security. This is especially the case in the developing nations where BUNV and NRIV are found, mainly in Africa. BUNVand BATV are fairly well characterized, while NRIV is not well characterized owing to only sporadic detection in human and animal populations in Africa. Reassortment is common among bunyaviruses, but NRIV is believed to be the only natural reassortant of the Bunyamwera serogroup. It resulted from a combination of BUNV S and L segments and the BATV M segment. This indicates at least some level co-circulation of BUNV and BATV, which have no historically been reported to overlap in geographic distributions. But as these viruses are undercharacterized, there remains a gap in the understanding of how such reassortment could occur, and the consequences of such. Due to their combined wide range of hosts and vectors, geographic distributions, potential severity of associated diseases, and potential for transmissibility between vertebrate hosts, these viruses represent a significant gap in knowledge with important One Health implications. The goal of this review is to report available knowledge of and identify potential future directions for study of these viruses. As these are collectively understudied viruses, there is a relative paucity of data; however, we use available studies to discuss different perspectives in an effort to promote a better understanding of these three viruses and the public and one health threat(s) they may pose.